الرقابة المالية كألية لحوكمة الميزانية العامة للدولة - mahboub, fatma; senoussi, samir (Finance and Business Economies Review, 2018)
If the concept of control is broad and its definition differs according to the scope of its use, since financial control means monitoring expenditures and revenues. It is almost the only type of control in the general budget of the state, before, during and after the financial work. Financial literature emphasizes that society must feel the positive impact of financial reform. In this context, financial control occupies an important place in the governance of the budget by raising the level of accountability and transparency